Clinical efficacy of oxidative stress correction by actovegin in diabetic polyneuropathy at type 2 diabetic patients with arterial hypertension - Ivan Petrovich Gorshkov (Endocrinology Research Centre, 2010)
Aim. To study Actovegin efficacy in oxidative stress (OS) correction at diabetic polyneuropathy (DPN) in patients with diabetes mellitus type 2 (DM2)and arterial hypertension (AH).Materials and Methods. 51 patients (24 women and 27 men) aged 53.4?0.7 with the average duration of DM2 5.6?0.2 years, DPN - 4.9?0.2years and AH - 6.0?0.2 years were examined. Daily albuminuria, glomerular filtration rate (GRF) were evaluated, standard methods for diagnosisof DPN were used. 26 patients took Actovegin therapy during 6-8 weeks, the rest 25 patients were in the control group. Parameters of the OS werestudied. Results. The increase of total oxidative capacity, the decrease of total antioxidant capacity and the rise of levels of antibodies to oxidated LDL wererevealed in patients with DM2, DPN and AH. Antioxidant and anti-hypoxic effects of 400 mg/day of Actovegin were established in this group of patients.Conclusions. Actovegin impacts oxidative stress parameters and improves the clinical manifestation of diabetic polyneuropathy.